PELATIHAN KONVERSI DATA MENGGUNAKAN DIGITAL TO ANALOG CONVERTER METODE TAHANAN BERBOBOT BINER DAN METODE LADDER - Kamolan, Aries; Sampebatu, Limbran (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The digital to analog converter module uses the binary weighted resistance method and the ladder method designed by Aries Kamolan makes it easy to convert data and see the process of changing digital data to analog data. By using this module, it is hoped that people will easily learn and be interested in this field and can distinguish digital data and analog data. The youth community who are members of the Bonggakaradeng Youth Association (HPBK) which is secretariat at BTN Risky housing, Kapasa sub-district, Tamalanrea sub-district, Makassar City, were chosen to be partners in this service because there are still many communities who cannot distinguish digital data and analog data and the use of these data and how to convert digital data to analog. The solution overcomes this problem by providing counseling and training to them using digital to analog converter modules using the binary weighted resistance method and the ladder method. The goal is that partners can easily perform data conversion and see the process of converting digital data to analog and introduce electrical engineering in the community. This activity went well even though the number of participants was not too much, but it seemed enthusiastic for HPBK members to take part in this training. HPBK members also want to know the basics of electrical science and the various electrical components in the module. They also expect this kind of activity again.